CTE-STEM 2022 conference proceedings - Specht, Marcus; Zhang, Xiaoling; Glahn, Christian; Fanchamps, Nardie (TU Delft Open, 2022)
The 6th APSCE International Conference on Computational Thinking and STEM Education 2022 (CTE-STEM 2022) is organized by the Asia-Pacific Society for Computers in Education (APSCE) and hosted by the Leiden-Delft-Erasmus Centre for Education and Learning (LDE-CEL). CTESTEM 2022 is hosted for the first time in Europe by the Delft University of Technology (TU Delft), Delft, the Netherlands. This conference continues from the success of the previous four international Computational Thinking conferences organized by the National Institute of Education and Nanyang Technological University (NIE/NTU). This conference invites CT as well as STEM researchers and practitioners to share their findings, processes, and outcomes in the context of computing education or computational thinking.